Effects of the R216Q mutation of GATA-1 on erythropoiesis and megakaryocytopoiesis - Balduini, Carlo L.; Pecci, Alessandro; Loffredo, Giuseppe; Izzo, Paola; Noris, Patrizia; Grosso, Michela; Bergamaschi, Gaetano; Rosti, Vittorio; Magrini, Umberto; Ceresa, Iride F.; Conti, Valeria; Poggi, Vincenzo; Savoia, Anna (Thrombosis and Haemostasis, 2004)
The transcription factor GATA-1, together with its cofactor FOG-1, regulates erythropoiesis and megakaryocytopoiesis. Mutations in the DNA or FOG-1 binding sites of its N-terminal zinc finger result in different illnesses. Alterations of the FOG-1 face are responsible for dyserythropoietic anemia with thrombocytopenia while R216Q, the only mutation identified in the DNA face, induces X-linked thrombocytopenia with thalassemia (XLTT). The former disorder has been studied in detail whereas little is known about the latter since only one family has been investigated. We studied a second family with an R216Q, showing that XLTT and dyserythropoietic anemia with thrombocytopenia, even if different clinical entities, are closely related disorders. In both cases, patients present mild dyserythropoiesis, red cell hemolysis, severely defective maturation of megakaryocytes, macrothrombocytopenia with α-granule deficiency, and abnormalities of the cytoplasmic membrane system. However, a thalassemia minor phenotype has only been described in patients with XLTT whereas severe anemia and thrombocytopenia with evident defects of platelet composition and function may be observed only in dyserythropoietic anemia with thrombocytopenia.
Keywords: GATA-1; thrombocytopenia; thalassemia; platelets; megakaryocytes